Contribuições do design estratégico para educação : um estudo sobre a Escola da Ponte e a Escola Projeto Âncora - Scroferneker, Camila Andrade (Universidade do Vale do Rio dos Sinos, 2018)
In this dissertation we seek to reflect on how strategic design can characterize the seed of a promising idea and to improve seeding strategies of social innovation, in the scope of education. Through cartography, we intend to describe and interpret the processes, principles and devices of the relationship between Escola da Ponte and Escola Projeto Âncora, to point out strategies developed by the two schools and to understand the relationships between the various actors involved in the creative ecosystem that contributed and still contribute to the process of learning and social innovation. For the accomplishment of our research w did a 5- day immersion in August 2017 at Escola Projeto Âncora. The research techniques used were: bibliographic and documentary research, direct observation and focused interview with semistructured questions. For the analysis of the interviews we used the technique of discourse analysis. After the description and interpretation of the collected data, we produced five cartographic tracks that in our view represent the sowing strategies used for the dissemination of a seed of social innovation.
Keywords: Design estratégico; Inovação social; Semeadura; Ecossistema criativo; Projeto Âncora; Strategic design; Social innovation; Seeding; Crative ecosystem; Projeto Âncora; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial